IT Infrastructure Modeling Language (ITML): A DSML for supporting IT management - Ulrich Frank; Monika Kaczmarek-Heß; Sybren de Kinderen (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2021)
In this research report, we present a new version of IT Modeling Language (ITML). It is integrated with the family of Domain-Specific Modeling Languages (DSMLs) that are part of Multi-Perspective Enterprise Modeling (MEMO). The design of the language followed a proven method. It provides for analysing requirements based on the analysis of possible use scenarios. The ITML was specified with the meta modeling language MEMO MML. Due to the considerable size of the meta model, its presentation is split into several partial meta models, which are described at a level of detail that is required for the implementation of the language within a modeling tool. The presentation of the meta model is supplemented by discussions of design conflicts and related decisions. In addition to the abstract syntax and semantics, which are represented by the meta model, we also propose a concrete syntax, which was designed with the support of a graphic designer. Finally, we also provide a short discussion of principal limitations of conventional meta modeling as well as an outlook on our future research.
urn:nbn:de:hbz:464-20220110-111514-6
Keywords: 650; IT management; enterprise modeling; IT infrastructure; ITML; MEMO; multi-levelmodeling